Immunized-Evolutionary Algorithm Based Technique for Loss Control in Transmission System with Multi-Load Increment - Sharifah Azwa Shaaya; Ismail Musirin; Shahril Irwan Sulaiman; Mohd Helmi Mansor (Institute of Advanced Engineering and Science, 2017)
Loss issue is significant in power system since it affects the operation of power system, which ultimately can be translated to monetary effect. Incremental demand that explicitly adding the reactive load causes extra heating losses in the transmission circuit. Without appropriate remedial control, the temperature increase on transmission line cable would end with insulation failure. This phenomenon can be alleviated with a proper compensation scheme that provides optimal solution along with avoidance of under-compensation or over-compensation. Evolutionary Programming (EP) has been recognised as one of the powerful optimisation technique, applied in solving power system problems. Nevertheless, EP is an old technique that sometimes could reach to a settlement that is not fully satisfied. Thus, the need for a new approach to improve the setback is urgent. This paper presents immunized-evolutionary algorithm based technique for loss control in transmission system with multi-load increment. The classical EP was integrated with immune algorithm so as to reduce the computational burden experienced by the classical EP. The algorithm has been tested on a IEEE 12-Bus System and IEEE 14-Bus System. Comparative study was conducted between EP and IEP in terms of optimisation performance. The optimal size and location of PV determined by IEP was able to control the loss in transmission system when the load increases. Results obtained from the studies revealed the merit of the proposed IEP; indicating its feasibility for future implementation in practical system.